Faktor yang Berhubungan dengan Hipertensi: Studi Cross-sectional di Wilayah Pedesaan Klakah, Lumajang, Jawa Timur : Factors Associated with Hypertension: A Cross-sectional Study in Rural Area of Klakah, Lumajang, East Java - Zahrah Febianti; Mauliya Sri Sukmawati Wahyudi; Cholis Abrori (Fakultas Kesehatan Masyarakat Universitas Tompotika Luwuk, 2022)
Hipertensi masih menjadi masalah kesehatan global karena prevalensinya yang tinggi dan komplikasinya yang fatal. Di Puskesmas Klakah, Kabupaten Lumajang, prevalensi hipertensi menempati urutan pertama kasus tertinggi penyakit tidak menular.Identifikasi faktor risiko hipertensi sangat berguna untuk manajemen dan pencegahan komplikasi hipertensi. Faktor risiko hipertensi ini dapat berbeda dominasinya antara wilayah yang satu dengan wilayah yang lainnya. Penelitian ini bertujuan untuk mengidentifikasi faktor yang berhubungan dengan hipertensi di wilayah pedesaan, Puskesmas Klakah, Lumajang, Jawa Timur. Jenis penelitian ini adalah analitik observasional dengan rancangan cross sectional dan mengambil data sekunder dari rekam medis pasien Puskesmas Klakah periode Januari-Oktober 2020. Sampel penelitian ini berjumlah 62, yang terdiri dari 31 responden hipertensi dan 31 responden non hipertensi. Rekam medis dipilih dengan menggunakan metode purposive sampling. Data rekam medis yang dianalisis meliputi umur, jenis kelamin, pekerjaan, tinggi badan, berat badan, tekanan darah, kadar asam urat. Data dianalisis menggunakan uji chi-square. Hasil penelitian menunjukkan bahwa sebagian besar penderita hipertensi di Puskesmas Klakah memiliki karakteristik usia >46-65 lansia, berjenis kelamin perempuan, memiliki aktivitas keseharian yang minimal, memiliki berat badan tidak obesitas, dan hiperurisemia. Hiperurisemia merupakan faktor yang berhubungan signifikan dengan hipertensi di masyarakat pedesaan yang tinggal di sekitar wilayah Puskesmas Klakah Kabupaten Lumajang dengan p=0.00, OR= 63,00 (95% CI = 12,87-308,18). Hypertension still becomes a global health problem due to its high prevalence and fatal complications. At a rural area of Klakah, Lumajang Regency, the prevalence of hypertension was atthe first rank of non-communicable diseases. Identification of risk factors is very useful for managing and preventing hypertensioncomplications. The hypertension risk factors may differ in dominance from one region to another. This study aims to identify the factors associated with hypertension at the rural area of Klakah Health Center, Lumajang, East Java. This is observational analytic research with a cross-sectional design. It used datas from patients’ medical records at the Klakah Health Center from January-October 2020. The sample was 62 respondents consisting of 31 hypertensive respondents and 31 non-hypertensive respondents. Medical records were selected using purposive sampling. Medical record data analyzed included age, gender, occupation, height, weight, blood pressure, and uric acid levels. The data wereanalyzed using the chi-square test. The results showed that most of the hypertensive patients at Klakah Health Center were characterized by aged>46-65 elderly, female, having minimal daily activities, not being obese, and having hyperuricemia. This study showed that hyperuricemia is significantly associated with hypertension in rural areas of Klakah Health Center, Lumajang Regency withp=0.00, OR= 63,00 (95% CI = 12,87-308,18). Hypertension still becomes a global health problem due to its high prevalence and fatal complications. At a rural area of Klakah, Lumajang Regency, the prevalence of hypertension was at the first rank of non-communicable diseases. Identification of risk factors is very useful for managing and preventing hypertension complications. The hypertension risk factors may differ in dominance from one region to another. This study aims to identify the factors associated with hypertension at the rural area of Klakah Health Center, Lumajang, East Java. This is observational analytic research with a cross-sectional design. It used datas from patients’ medical records at the Klakah Health Center from January-October 2020. The sample was 62 respondents consisting of 31 hypertensive respondents and 31 non-hypertensive respondents. Medical records were selected using purposive sampling. Medical record data analyzed included age, gender, occupation, height, weight, blood pressure, and uric acid levels. The data were analyzed using the chi-square test. The results showed that most of the hypertensive patients at Klakah Health Center were characterized by aged>46-65 elderly, female, having minimal daily activities, not being obese, and having hyperuricemia. This study showed that hyperuricemia is significantly associated with hypertension in rural areas of Klakah Health Center, Lumajang Regency with p=0.00, OR= 63,00 (95% CI = 12,87-308,18).